The Procoagulant in Human Urine: Purification, Assay and Some Biochemical and Physiological Properties - Aoki, N; von Kaulla, K. N (Thrombosis and Haemostasis, 1966)
A powerful procoagulant is excreted with the human urine. The purification, assay with purified prothrombin, definition of unit, properties and animal studies are described. The material is relatively heat resistent, and it activates prothrombin in presence of Ac-globulin and platelet factor 3 or platelet substitute (brain lipid). Fresh male human urine contains 10 u/ml. One to 4 u/ml are required to normalize clotting of hemophilic plasma. Purified preparations exhibit a specific activity around 11,000 u/mg tyrosine. Intravenous injections or infusions of the procoagulant into dogs or rabbits induce for a few hours a phase of transitory hypercoagulability as indicated by shortening of recalcification time and enhancement of prothrombin consumption. This is followed in the rabbit by the appearance of a circulating “antithromboplastin”.